2016
DOI: 10.1155/2016/6157605
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress: An Effective Prognostic Tool for an Early Detection of Cardiovascular Disease in Menopausal Women

Abstract: Background. Menopause, a form of reproductive aging, is marked by many hormonal variations which cause imbalance in the oxidative processes resulting in onset of endothelial dysfunction leading to cardiovascular disease (CVD). We aimed to analyze the effect of oxidative stress in an early detection of CVD in all menopausal women both normolipidemic and hyperlipidemic. Methods and Results. Study included 523 menopausal women (265 CVD and 258 non-CVD). They were screened for lipid profile, serum malondialdehyde … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…[ 21 ] Other studies revealed that AIP was positively associated with blood uric acid and C-reaction protein and was strongly associated with oxidative stress. [ 22 , 23 ] In recent years, a growing body of evidence has indicated that AIP is a strong marker to predict the risk of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] Other studies revealed that AIP was positively associated with blood uric acid and C-reaction protein and was strongly associated with oxidative stress. [ 22 , 23 ] In recent years, a growing body of evidence has indicated that AIP is a strong marker to predict the risk of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, AIP was identified as a powerful predictor of the risk of fatty liver [23]. Additionally, AIP correlates positively with serum uric acid, C-reactive protein, and oxidative stress [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation and protein oxidation due to increased ROS production, result in overexpression of redox genes, intracellular calcium overload and DNA fragmentation, causing damage to vascular smooth muscle cells (VSMCs), endothelial cells or myocardial cells [37,[41][42][43]. In addition, lipid peroxidation is also actively involved in the peroxidative modification of low-density lipoprotein (LDL) [37,[41][42][43], that when oxidized (i.e., oxidized LDL) plays a key role in the development of atherosclerosis [44]. Moreover, Zembron-Lancy et al [32], have recently shown that levels of oxidized low density lipoprotein (oxLDL), protein carbonyls (PC) and lipid peroxidases (LPO) were elevated in elderly men and were highly correlated with common CVD factors such as LDL, high-density lipoprotein (HDL) and Framingham score.…”
Section: Oxidative Stress and Cardiovascular Diseasementioning
confidence: 99%
“…Nevertheless, it has been noticed that several markers of oxidative stress in plasma were increased in CVD patients [46], while plasma levels of oxLDL is considered to be a prognostic indicator of mortality in subjects with congestive heart failure [46,47]. In addition, many oxidative stress biomarkers, such as serum lipid hydroperoxides, plasma malondialdehyde (MDA) or urine F2-isoprostanes, are utilized as a prognostic tool for assessing the risk of CVDs [15,41]. A recent study showed a significant increase in MDA, oxLDL and PC, and a significant decrease in superoxide dismutase (SOD) activity, in menopausal women with CVD as compared to their healthy counterparts [41].…”
Section: Oxidative Stress and Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation